Representasi Pegawai Perjanjian Waktu Tertentu dalam menghadapi Kecemasan Ketidakpastian Bekerja - Indra Saripudin; Azhar Savero Sukma; Ma’qul Hadhqun Fasha; Agianto Aji Pamungkas (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the impact of Fixed-Term Employment Agreements (PKWT) on the anxiety of uncertainty experienced by employees, as well as how it affects their productivity in the workplace. In an era of economic uncertainty and labor market dynamics, employees with fixed-term employment agreements (PKWT) often face significant anxiety about their job security, as they lack the job stability enjoyed by permanent employees. The research participants were contract workers at a private company in the Tangerang area. This study explores how PKWT employees feel anxiety about job uncertainty, the effectiveness of PKWT in increasing employee productivity, and the problems that arise from this uncertainty. The method used was a qualitative study through in-depth interviews with PKWT employees and employment management. According to the study's findings, employee motivation and mental health were not significantly affected by anxiety related to job insecurity. This study is expected to provide recommendations to help management create policies that can reduce anxiety and improve the performance of PKWT employees.